2011
DOI: 10.1089/jmf.2010.0206
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc Bioaccumulation and Bioavailability of Ganoderma lucidum

Abstract: Ganoderma lucidum is a widely recognized medicinal mushroom. The bioaccumulation and potential bioavailability of copper (Cu) and zinc (Zn), which are essentials for human health, were analyzed in G. lucidum mycelium and fruit bodies grown in the presence of these metals to test their potential utility as a food dietary supplement. Mycelia grown in culture medium with non-mycotoxic doses of Cu or Zn (25 and 50 mg/kg) were selected for evaluation of the bioavailability of these metals in the gastrointestinal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
2
13
0
3
Order By: Relevance
“…Matute et al (2011) obtained bioavailability of 31.5 and 30.7% copper and zinc, respectively, in G. lucidum cultivated on substrate supplemented with 100 mg/kg copper and 25 mg/kg zinc. Thus, a great variability in the bioavailability was observed depending upon the supplemented mineral and the mushroom variety.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Matute et al (2011) obtained bioavailability of 31.5 and 30.7% copper and zinc, respectively, in G. lucidum cultivated on substrate supplemented with 100 mg/kg copper and 25 mg/kg zinc. Thus, a great variability in the bioavailability was observed depending upon the supplemented mineral and the mushroom variety.…”
Section: Discussionmentioning
confidence: 84%
“…In G. lucidum, cultivated on sunflower seed hulls and barley, there was an increase of BE with the addition of 100 mg/kg copper (Matute et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon can be used in biofortification strategies in mushroom cultivation and result in their increased nutritional value or biological activity. A number of studies have already demonstrated that this approach can be employed to enrich the fruiting bodies of selected species with elements such as copper in Ganoderma lucidum [4]; iron (Fe) in Pleurotus ostreatus, P. cornucopiae, P. djamor, P. pulmonarius or P. djamor v. roseus [5]; lithium (Li) in G. lucidum, P. eryngii and P. ostreatus [6,7]; potassium (K) in P. eryngii, Flammulina velutipes or Hypsizygus marmoreus [8]; selenium (Se) in A. bisporus, P. eryngii, P. ostreatus, Pholiota nameko [9,10] and zinc (Zn) in G. lucidum and P. ostreatus [11]. Particular attention has been paid to substrate supplementation with inorganic Se salts as such an approach appears to potentially increase antioxidant, immunomodulatory and anticancer activities of selected mushrooms species [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The more weight of Ganoderma mushroom is due to its high water content up to 90%, which makes extracts of mushroom dehydrated powder and residual 10% of its mass consist of protein (10-40%), carbohydrate (3-28%), fiber (3-32%), fat (28%), and ash (8-10%). Besides, various other compounds such as provitamin D2 [9], C19 fatty acids [10], and essential nutrients such as copper and zinc [11] have also been found to be present. With the minerals potassium, calcium, phosphorous, magnesium, selenium, iron, zinc, and copper represent most of the mineral content [12,13].…”
Section: Introductionmentioning
confidence: 99%